Chinese Ethnic Family Entrepreneurship Education Pattern: Study of SMK students in Pasuruan - Rachmad Hidayat; Danardana Murwani; Mohammad Arief (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2019)
The purpose of this study was to reveal the pattern of entrepreneurship education in Chinese ethnic families of SMK students at Negeri 1 Pasuruan. The research approach was a descriptive qualitative case study. The results of the study showed that Chinese ethnic students' families taught their children entrepreneurship from childhood by getting used to participating in business practices that had been done, family education was able to shape students' perspectives to be more open and broad-minded, key principles taught was the unique values that they had been held and believed for generations. The element of the entrepreneurial spirit that was formed includes self-confidence, willingness, and interest in entrepreneurship, and locus of control.